Bu-Shen-Ning-Xin decoction: inhibition of osteoclastogenesis by abrogation of the RANKL-induced NFATc1 and NF-κB signaling pathways via selective estrogen receptor α - Wang L; Qiu XM; Gui YY; Xu YP; Gober HJ; Li DJ (Dove Medical Press, 2015)
Ling Wang,1,2,* Xue-Min Qiu,1,2,* Yu-Yan Gui,1,2 Ying-Ping Xu,1,2 Hans-Jürgen Gober,3 Da-Jin Li11Laboratory for Reproductive Immunology, Hospital and Institute of Obstetrics and Gynecology, IBS, Fudan University Shanghai Medical College, 2Shanghai Key Laboratory of Female Reproductive Endocrine Related Diseases, Shanghai, People’s Republic of China; 3Department of Pharmacy, Wagner Jauregg Hospital and Children’s Hospital, Wagner Jauregg Weg, Linz, Austria*These authors contributed equally to this workIntroduction: Bu-Shen-Ning-Xin decoction (BSNXD) is a traditional Chinese medicinal composition that has been used as a remedy for postmenopausal osteoporosis, but the mechanisms affecting bone metabolism are not fully understood.Purpose: We investigated the molecular mechanism and signaling pathway underlying the effect of BSNXD on osteoclastogenesis.Materials and methods: A postmenopausal osteoporosis animal model generated by ovariectomy was administered BSNXD and drug-derived serum was prepared. An enzyme immunoassay was conducted to measure the 17-β-estradiol (E2) concentration in the drug-derived serum. Bone marrow-derived monocyte/macrophage precursor cells were treated with drug-derived serum, and tartrate-resistance acid phosphatase staining was conducted to observe osteoclastogenesis. A bone resorption assay was performed to analyze the effect on osteoclastic resorptive function. Real-time PCR, flow cytometry, Western blotting, transfection, and luciferase assays were conducted to explore the related mechanism.Results: E2 was not elevated in BSNXD-derived serum. BSNXD-derived serum suppressed receptor activation of nuclear factor κB ligand (RANKL)-activated osteoclastogenesis in a dose-dependent manner; this effect could be reversed by estrogen receptor α antagonist methyl-piperidino-pyrazole. The serum suppressed RANKL-induced NF-κB transcription and inhibited the accumulation of nuclear factor of activated T-cells, cytoplasmic 1 in osteoclast precursor cells; the inhibitory effect was abolished by methyl-piperidino-pyrazole but not the estrogen receptor β antagonist or androgen receptor antagonist.Conclusion: These results collectively suggest that administration of BSNXD presents inhibitory effects on osteoclast differentiation by abrogating the RANKL-induced nuclear factor of activated T-cells, cytoplasmic 1 and NF-κB signaling pathways downstream of estrogen receptor α, thereby contributing to the inhibitory effect on bone resorption.Keywords: herbal formula, osteoclastogenesis, estrogen receptor α, NF-κB, NFATc1